Palmitoylated transmembrane adaptor proteins in leukocyte signaling - Stepanek, Ondrej; Draber, Peter; Horejsi, Vaclav (Cellular signalling, 2014)
Transmembrane adaptor proteins (TRAPs) are structurally related proteins that have no enzymatic function, but enable inducible recruitment of effector molecules to the plasma membrane, usually in a phosphorylation dependent manner. Numerous surface receptors employ TRAPs for either propagation or negative regulation of the signal transduction. Several TRAPs (LAT, NTAL, PAG, LIME, PRR7, SCIMP, LST1/A, and putatively GAPT) are known to be palmitoylated that could facilitate their localization in lipid rafts or tetraspanin enriched microdomains. This review summarizes expression patterns, binding partners, signaling pathways, and biological functions of particular palmitoylated TRAPs with an emphasis on the three most recently discovered members, PRR7, SCIMP, and LST1/A. Moreover, we discuss in silico methodology used for discovery of new family members, nature of their binding partners, and microdomain localization.
Keywords: lidé; SCIMP; Lipoylation; adaptorové proteiny signální transdukční; Signal Transduction; Humans; Palmitoylation; Membrane Microdomains; Adaptor; signální transdukce; lipoylace; PRR7; membránové proteiny; LST1; Membrane Proteins; Leukocytes; leukocyty; membránové mikrodomény; Adaptor Proteins, Signal Transducing; LAT